A comparative study of the structural, optical, magnetic and magnetocaloric properties of HoCrO3 and HoCr0.85Mn0.15O3 orthochromites. Issue 6 (15th March 2021) - Kanwar, Komal; Coondoo, Indrani; Anas, M.; Malik, Vivek K.; Kumar, Pradip; Kumar, Sandeep; Kulriya, Pawan K.; Kaushik, S.D.; Panwar, Neeraj
Abstract: In the present study, the physical properties including structural, optical and magnetic of HoCr1-x Mnx O3 (x = 0, 0.15) have been thoroughly investigated and compared. A detailed structural analysis of the compounds provided a way to correlate the optical and magnetic properties with the change in Cr-site ionic radius, tilt angles and distortion in CrO6 octahedra due to Mn substitution. Further, the shift in the Raman phonon modes was associated with the increased structural distortion owing to Mn substitution in HoCrO3 compound. The variation in the Urbach energy values, measured from the diffuse reflectance spectroscopy, was found to be closely related to the octahedral distortion. The optical band gap reduced from 3.22 eV to 2.01 eV after Mn substitution. Other optical parameters such as skin depth, refractive index, extinction coefficient and optical conductivity were also perceived to vary noticeably in the substituted compound. The overall structural distortion with Mn substitution resulted in the decrease of antiferromagnetic transition temperature of the pristine compound. The strong magnetic entropy change was observed at low temperatures in pure HoCrO3 compound and its value was enhanced on Mn substitution. Therefore, the present work provides a convenient method to tune the multifunctional properties of HoCrO3 compound, which has practical applications such as photocatalyst and low-temperature magnetic refrigerant.